Herbicidal Activity of Smoke Water - Garrido, Raphael Mota [UNESP]; Dayan, Franck Emmanuel; Kolb, Rosana Marta [UNESP] (MDPI, 2023)
Weeds cause more crop yield loss and increase farmers’ production costs more than any other agricultural pest worldwide. Natural extracts can be an important alternative to synthetic herbicides, or they can be one of the resources from which to discover new pesticide leads. The phytotoxic potential of smoke water was evaluated regarding germination and initial growth, prospecting for its possible herbicidal activity in weeds. Herbicidal activity was evaluated through germination, initial growth, and seedling vigor index bioassays in the laboratory and emergency with initial development bioassays in a greenhouse with smoke water solutions at 2.5, 5, 10 and 20% v/v. Experiments with two treatments were analyzed using T-tests for the parametric data and the Mann–Whitney test for the non-parametric data (p < 0.05). Experiments with three treatments or more were analyzed with a one-way ANOVA test followed by a Tukey test for the parametric data and a Kruskal–Wallis test followed by a Dunn test for the non-parametric data (p < 0.05). Linear regression was used to analyze data from the time–injury curve. The greatest effect on germination suppression (98%) was achieved when the Amaranthus viridis seeds were germinated in the laboratory with a 10% smoke water solution. Germination of Raphanus raphanistrum and Digitaria insularis was reduced by 93 and 75%, respectively, at this concentration. In greenhouse experiments, emergence of A. viridis was inhibited 81% by 20% smoke water. In laboratory initial growth experiments, 5% smoke water had the greatest inhibitory effect (94%) on A. viridis. R. raphanistrum initial growth reduction was 82%, Urochloa decumbens was 80%, D. insularis was 77% and Emilia fosbergii was 70% in the same conditions. In greenhouse development experiments, 70% of the A. viridis plants were killed by 5% smoke water treatment. These plants had 88% injury after treatment with 5% smoke water. Therefore, these findings suggest that smoke water solutions have potential as an herbicide, inhibiting the germination and initial growth of monocotyledonous and eudicotyledonous weeds. However, field tests are needed to confirm the potential of smoke water as an herbicide.
Keywords: injury; phytotoxic potential; smoke water; weed